2014
DOI: 10.1111/tpj.12392
|View full text |Cite
|
Sign up to set email alerts
|

Lack of isocitrate lyase in Chlamydomonas leads to changes in carbon metabolism and in the response to oxidative stress under mixotrophic growth

Abstract: SUMMARYIsocitrate lyase is a key enzyme of the glyoxylate cycle. This cycle plays an essential role in cell growth on acetate, and is important for gluconeogenesis as it bypasses the two oxidative steps of the tricarboxylic acid (TCA) cycle in which CO 2 is evolved. In this paper, a null icl mutant of the green microalga Chlamydomonas reinhardtii is described. Our data show that isocitrate lyase is required for growth in darkness on acetate (heterotrophic conditions), as well as for efficient growth in the lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 55 publications
7
81
0
1
Order By: Relevance
“…Support for this proposal comes from the recent study of an ICL1 deletion mutant (61), which is devoid of a glyoxylate cycle and displays many anomalies in central carbon metabolism.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Support for this proposal comes from the recent study of an ICL1 deletion mutant (61), which is devoid of a glyoxylate cycle and displays many anomalies in central carbon metabolism.…”
Section: Resultsmentioning
confidence: 98%
“…Hence sensitive genes displaying a strong acetate boost prove to also display a strong transcriptional sensitivity to the presence/absence of exogenous acetate. Notably, 7 of these 13 proteins, listed in the previous paragraph, are also expressed aberrantly in the ICL1 mutant (61).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies implicated the TCA pathway in carbon utilization and lipid accumulation. A Chlamydomonas mutant missing isocitrate lyase, a key enzyme in the glyoxylate shunt within the TCA cycle, was found to have acetate-specific growth defects and to overaccumulate lipids (Plancke et al, 2014). A metabolic modeling study also found that changes in TCA flux were required to maintain metabolic balance when switching from phototrophic to mixotrophic growth (Chapman et al, 2015).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 93%
“…The glyoxylate cycle plays an essential role in acetate metabolism and also allows for bypass of OGDH. Plancke et al created a mutant of the green algae Chlamydomonas that lacked an isocitrate lyase gene [31]. They found that this mutant strain lost its ability to grow on acetate.…”
Section: Impacts Of Thiamine and Hmp On Algal Central Metabolism In Amentioning
confidence: 99%